Active factors in dance/movement therapy: specifying health effects of non-goal-orientation in movement - Dahlheimer, Solveig; Koch, Sabine C. (The arts in psychotherapy, 2016)
This study addresses the impact of non-goal-directed improvisational dance versus goal-directed improvisational dance in reducing perceived stress and improving well-being, general self-efficacy, and body self-efficacy. Fifty-seven students participated either in the experimental condition (N=30) or in the control condition (N=27). Participants in the experimental group (EG) performed non-goal-directed improvisational dance movements, while participants in the control group (CG) improvised to the same music in a goal-directed way with the help of colored paper sheets serving as targets. In support of the hypothesis, perceived stress decreased (p<0.05) and body self-efficacy increased (p<0.05) in the EG vs. the CG. At post-test, all outcomes improved within the EG (perceived stress and well-being: p<0.001; body self-efficacy: p<0.01; self-efficacy: p=0.001); and within the CG perceived stress decreased (p<0.01), and well-being (p<0.001), and self-efficacy (p<0.05) increased. Results suggest that non-goal-directed vs goal-directed improvisational dance is effective in improving body self-efficacy, and is superior in reducing perceived stress. Moreover, improvisational dance generally seems to have beneficial effects on health-related psychological outcomes. Future studies should investigate implications for clinical settings, identify other active factors of dance therapy, and anchor them theoretically.